Finite Element Analysis of Rock-Cutter Interaction in Drilling Operation using Single Cutter PDC Bit - Nawawi, Muhammad Farhan (2018)
Polycrystalline diamond compact (PDC) bit have been used more than 60% for oil and gas drilling operations worldwide. Despite the advantages of the famous PDC bit, the latest PDC bit design configuration is still yet to be proven compatible towards deeper and harder rock formations. Starting from the year 1990, the oil productions in shallow depth are decreasing whiles the oil productions in deep water starting to increase. Drilling in deep formations with the presence of variable rock hardness will shorten the tool life and lower the tool’s performance. The research focuses on identifying the optimum design parameters for single cutter PDC bit with the respect to the rate of penetration (ROP). Costly and time consuming experimental setup scopes the research toward finite element analysis (FEA) using ANSYS explicit dynamics. The simulation results shows that the optimum design for single cutter PDC bit is at the orientation of 30° back rake angle with 2mm depth of cut (DOC) which able to provide low horizontal contact force and high ROP. The simulation parameters of the single cutter limit the testing towards obtaining stable vertical force results. In the future, it is recommended to continue the FEA by including the vertical force data and move forwards towards laboratory testing.